THE EFFORTS TO ENCOURAGE INNOVATION THROUGH THE WELFARE OF EMPLOYEES AND WORK CULTURE IN THE ONLINE LOAN INDUSTRY - Insan, Wahyu; Khaeruman, Khaeruman; Susanto, Budi (Yayasan Education and Social Center, 2024)
Human resource management is the process of dealing with various problems in the workplace so that company activities can be supported to achieve predetermined goals. Humans constitute one of the components of the organization, consisting of individuals employed by the organization. This study seeks to assess initiatives that promote innovation via Employee Welfare and Work Culture within the online loan sector at PT Amaan Indonesia Sejahtera, Branch of Serang. The method used was a quantitative survey using SPSS 29 software, with a population of 48 respondents and a saturated sample. The results showed that the Employee Welfare variable 3,150 and Work Culture variable 2,993 were all greater than Table 1.679, so Ho was rejected. The Fcount value is 28.135, greater than Ftable 3.20, which means Ho is rejected. Partially, the Employee Welfare and Work Culture variables encourage innovation, and simultaneously, these two variables also encourage employee innovation at PT Amaan Indonesia Sejahtera, Serang Branch